PROFIL PENGGUNAAN CHOP DAN RCHOP PADA PASIEN LIMFOMA NON-HODGKIN DI RSUP DR. SARDJITO - Gustinanda, Rizky; Khair, Riat El; Irham, Lalu Muhammad; Supadmi, Woro (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Non-Hodgkin lymphoma (LNH) is a heterogeneous malignancy of the lymphatic system with CHOP and RCHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, Prednisolone) chemotherapy regimens as main options. Local data on patient characteristics undergoing these treatments are still limited, especially at Dr. Sardjito General Hospital. This study evaluates the characteristics of LNH patients receiving both regimens at Dr. Sardjito (2020–2023). It is a descriptive observational study with a cross-sectional design. Data from patient medical records were analyzed descriptively. Of 176 patients, 80 received CHOP and 96 R-CHOP. Most were male (CHOP: 70%; R-CHOP: 60.4%) and aged >50 years, with peak age of 51–60 in CHOP (40%) and >60 in R-CHOP (44.8%). Comorbidities were found in one-third of patients. Advanced stage predominated (CHOP: 31.3% stage 4; R-CHOP: 38.5% stage 2), and most completed 6 chemotherapy cycles. Rituximab ≥550 mg was widely used in R-CHOP; cyclophosphamide >1100 mg, doxorubicin 70–79 mg, and vincristine ≥2 mg were standard in both regimens. Prednisone 100 mg was common. Diffuse Large B-Cell Lymphoma (DLBCL) dominated R-CHOP (98.96%), while CHOP patients included DLBCL (38.75%), FL, PTCL-NOS, and others. Findings highlight the importance of individualized treatment based on histopathology and disease stage.